Sepsis at ICU Admission Increases the ICU Mortality Rates Among Very Long ICU Stay Patients: A Secondary Analysis - Farshid Rahimibashar; Mahmood Salesi; Amir Vahedian-Azimi; Masoum Khosh Fetrat (Baqiyatallah University of Medical Sciences, 2020)
Background: Sepsis is a very common serious medical condition among patients admitted to the intensive care units (ICUs) that increases with age and ICU length of stay (LOS). Objectives: The primary goal of this study was to estimate the mortality rate due to sepsis among adult patients admitted to the mixed medical-surgical ICUs for a long time. The secondary goal was to identify factors associated with predicting ICU mortality in individuals with long-term ICU LOS. Methods: Adult patients admitted to the medical ICU for a long time (≥75 days) were included in this retrospective secondary analysis study. Baseline demographic, clinical, and laboratory data were recorded upon inclusion in the study. Results: ICU mortality occurred in 78 (43.1%) patients, out of 188 participants. A greater portion of patients with sepsis at admission (62.7%) were observed in the death group (59.2% vs. 30.8%, P < 0.001), than the survivor group. Additionally, survived patients differed significantly in terms of age, family engagement, baseline cognitive impairment, activity, nurse anticipated turnover scale (ATS), duration of a mechanical ventilator (MV), and ICU LOS. The results of multivariate binary logistic regression showed that the older age and low family intervention can increase the risk of mortality in patients with sepsis at the time of admission, with a long ICU LOS. Conclusion: Our findings are crucially important to increase the awareness of the impact of sepsis, highlight the need for continued research into potential preventive and therapeutic interventions, and help guide resource allocation.